In Vitro Tissue‐Engineered Skeletal Muscle Models for Studying Muscle Physiology and Disease. Issue 15 (25th April 2018) - Khodabukus, Alastair; Prabhu, Neel; Wang, Jason; Bursac, Nenad
Abstract: Healthy skeletal muscle possesses the extraordinary ability to regenerate in response to small‐scale injuries; however, this self‐repair capacity becomes overwhelmed with aging, genetic myopathies, and large muscle loss. The failure of small animal models to accurately replicate human muscle disease, injury and to predict clinically‐relevant drug responses has driven the development of high fidelity in vitro skeletal muscle models. Herein, the progress made and challenges ahead in engineering biomimetic human skeletal muscle tissues that can recapitulate muscle development, genetic diseases, regeneration, and drug response is discussed. Bioengineering approaches used to improve engineered muscle structure and function as well as the functionality of satellite cells to allow modeling muscle regeneration in vitro are also highlighted. Next, a historical overview on the generation of skeletal muscle cells and tissues from human pluripotent stem cells, and a discussion on the potential of these approaches to model and treat genetic diseases such as Duchenne muscular dystrophy, is provided. Finally, the need to integrate multiorgan microphysiological systems to generate improved drug discovery technologies with the potential to complement or supersede current preclinical animal models of muscle disease is described. Abstract : Human tissue‐engineered skeletal muscles hold promise as a novel tool to study muscle pathophysiology in vitro. Herein, the biology of muscle development is reviewed and the progress made in generating functional human engineered muscle tissues from primary and induced pluripotent stem cells is highlighted. The utility of these microphysiological systems for disease modeling and patient‐specific drug development is further discussed.